THE SOURCE OF ERRORS IN INDONESIAN-ENGLISH TRANSLATION - Utami, Silvia (Jurnal KATA, 2017)
This research aimed to identify types of translation errors and to find out the sources of errors (interlingual and intralingual errors) in Indonesian-English translation written by the students. The type of this research was descriptive research which used Error Analysis procedures to identify and analyze the students’ error. The findings showed that the types of grammatical errors made by the students in their translation were three types, namely global errors, local errors, and other errors. The most frequent error made by the students was local errors and the fewest error made by the students was other errors.  Then, this research revealed that mostly errors occurred in students’ translation were caused by intralingual error. Meanwhile, only few errors were caused by interlingual error. The errors occured due students’ incomplete knowledge of the target language.